2010
DOI: 10.1103/physrevb.82.094506
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transition, metallization, and superconductivity in boron triiodide

Abstract: Pressure evolution of structural and electrical properties of boron triiodide, a highly anisotropic molecular crystal consisting of stacked layers of planar BI 3 molecules, has been studied by x-ray diffraction and resistivity measurements. A new phase transition was observed to occur at 6.2 GPa from the molecular phase with hexagonal structure to a monatomic phase with the face-centered-cubic lattice of iodine atoms. This first-order phase transition is characterized by the discontinuous crush of stacking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(21 reference statements)
3
16
0
Order By: Relevance
“…This cell cannot represent the actual unit cell due to the number of iodine atoms, 4 atoms per cell in the fcc lattice. For this reason, the volume of the fcc cell was normalized to the volume per formula unit (V PFU ), i.e., V PFU = 3V fcc /4 following the same analysis used by Hamaya et al 24 for the high pressure phase of BI 3 . The pressure dependent V PFU is shown in the plot of Figure 8.…”
Section: B Alimentioning
confidence: 99%
See 1 more Smart Citation
“…This cell cannot represent the actual unit cell due to the number of iodine atoms, 4 atoms per cell in the fcc lattice. For this reason, the volume of the fcc cell was normalized to the volume per formula unit (V PFU ), i.e., V PFU = 3V fcc /4 following the same analysis used by Hamaya et al 24 for the high pressure phase of BI 3 . The pressure dependent V PFU is shown in the plot of Figure 8.…”
Section: B Alimentioning
confidence: 99%
“…There are additional materials aspects worth pursuing too. A recent high-pressure study of boron triiodide (BI 3 ) 24 concluded that a high-pressure phase exists above 6.2 GPa that becomes metallic and superconducting with T c = 1 K above 23 and 27 GPa, respectively. Yao and Klug 25 attributed the appearance of superconductivity to the coordination change from planar BI 3 monomers to B 2 I 6 dimers, i.e., isostructural to ambient phase of AlI 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The transition pressure of about 5.4 GPa for the BI 3 P6 3 /m phase to the P1 structure is in good agreement with the recently reported experimental value of 6.2 GPa. 12 Predicted transition pressures for BBr 3 and BCl 3 solids are at 9 and 15 GPa, respectively. It is interesting to note that, for phase transitions in the alkali halides and hydrides, the transition pressures for NaCl-to CsCl-type structures also decreases with increasing alkali-metal atomic number.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…12 A recent density functional theory (DFT) study 13 has predicted a B 2 I 4 (μ-I) 2 molecular solid structure to form at high pressure. This structure is consistent with all of the basic features of the experimental study, 12 suggesting that the first new pure-phase binary trihalide of boron has been prepared in more than a century. (The last of the binary boron(III) halides, BI 3 , has been known since 1891.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation